STUDENTS’ AWARENESS AND UTILISATION OF ELECTRONIC BOOKS IN UiTM CAWANGAN PULAU PINANG - Noor Aina Abdul Razak; Hayati Moktaram (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
To provide open access to electronic resources, academic libraries spend millions each year. Free e-books may not keep students interested in and using them, despite the fact that they are available for free. In fact, the librarians at Perpustakaan Tun Abdul Razak (PTAR) found that students did not fully utilize the e-books available. Thus, they requested a survey to be conducted for students at Universiti Teknologi MARA, Cawangan Pulau Pinang (UiTMCPP) on their e-book awareness and usage. The goal of this study is to identify the reasons why students use and avoid using e-books. More than 200 students at UiTMCPP completed this survey about how they use e-books for learning, how they search for them, what devices that they use to obtain them, and how they read and utilise them. Results show that more than half of the students prefer e-books because they are free and easy to use, while others prefer paper books because they are more convenient. Most students also are aware of and use the library’s e-book collection to its fullest, according to the survey results.